Doping Effect of Lead(II) on Structural and Optical Properties of Chromium Oxide Nanoparticles - Kalaiselvi, N.; Madhu, K.U. (Asian Journal of Chemistry, 2020)
In this work, the effects of doping post transition metal (Pb2+) on the structural, morphological, elemental and optical properties of pure chromium oxide nanoparticles are reported. The structural and morphological properties were examined by X-ray diffraction and scanning electron microscopy (SEM). The elemental composition of the prepared nanoparticles were estimated from energy dispersive X-ray (EDX) absorption spectra. The band gap energies of the prepared nanoparticles (4.72-3.78 eV) obtained from UV-vis absorption spectroscopy is higher than that of bulk Cr2O3 (3.3 eV), which ensures that the prepared nanoparticles were successfully synthesized in the nano-region.